‘Affirmative Signalling’: Dickens’s railway journalism and Victorian risk society - Martin, Daniel (My University, 2017)
This essay explores Charles Dickens’s railway journalism of the 1850s and 1860s and its differences from his more well-known fictional accounts of the British railway network. While fictional works such as Dombey and Son and ‘The Signalman’ emphasize the catastrophic aspects of railway accidents, Dickens’s journalism in Household Words and All the Year Round examines the modern systematicity of the railway network, which by its nature as system, necessitated accidents on the lines. The essay incorporates theoretical readings of risk by Ulrich Beck and Paul Virilio into its critical assessment of Dickens’s railway journalism. Fundamentally, it aims to demonstrate that Dickens’s railway journalism illuminates the complexity of Victorian narratives of technological and bureaucratic industrial and transport systems by prioritizing the global dimensions of systematic accidents over the period’s tendencies to focus merely on local accidental events.
Keywords: journalism; Charles Dickens; railway network; railways; risk society; accidents; media; Ulrich Beck; Paul Virilio